Preparing for the future: An examination of healthcare provider and patient communication regarding childhood cancer survivorship. (22nd October 2014) - Lamanna, J.; Trapp, S.; Russell, C.; Stern, M.
Abstract: Background: This qualitative, exploratory study examines the content of communication between healthcare providers (HCP) and childhood cancer patients (CCP) during a medical appointment to evaluate the extent to which cancer survivorship issues (medical and psychosocial) are discussed. Methods: The content of the communication for 16 CCP ages 10–22 and their HCP were examined via audio recorded medical appointments occurring within 6 months of the end of active cancer treatment. The data were analysed using template analysis, a constructivist‐interpretivist qualitative approach. Results: HCP addressed more medically focused than psychosocially focused issues related to survivorship. Conclusions: Most discussions of survivorship are medically focused, potentially leaving patients with little information about future psychosocial functioning. Recommendations for future research on enhancing discussions about psychosocial issues are presented. This research has the potential to inform future interventions to enhance patient–provider communication on survivorship issues.